2019
DOI: 10.1515/cclm-2018-1146
|View full text |Cite
|
Sign up to set email alerts
|

Collection, transport and storage procedures for blood culture specimens in adult patients: recommendations from a board of Italian experts

Abstract: Bloodstream infections (BSIs) remain a potentially life-threatening condition. The gold standard for the diagnosis of BSI is still blood cultures (BCs), and the diagnostic yield depends on clinical and technical factors that have an impact on collection and transportation. Hence, monitoring of the entire pre-analytical process from blood collection to transportation to the microbiology laboratory is critical. To optimize the clinical impact of the diagnostic and therapeutic procedures, a multidisciplinary appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 76 publications
0
13
0
Order By: Relevance
“…The number of cold or heat packs added to the package can change the thermal profile, and we identified an optimal condition for both blood and urine transportation packaging. The presented transportation protocol takes into consideration the clinical and technical factors that may have an impact on collection and transportation as detailed in other studies 9 , 10 .…”
Section: Discussionmentioning
confidence: 99%
“…The number of cold or heat packs added to the package can change the thermal profile, and we identified an optimal condition for both blood and urine transportation packaging. The presented transportation protocol takes into consideration the clinical and technical factors that may have an impact on collection and transportation as detailed in other studies 9 , 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also shown that the amount of blood obtained for culturing has an influence on the number of false-negative and false-positive blood cultures. According to De Plato et al [ 22 ], volume of blood is the most important parameter when detecting microorganisms in the bloodstream. They have recommended 30–40 ml of blood obtained in total, distributed into two aerobic and two anaerobic bottles.…”
Section: Discussionmentioning
confidence: 99%
“…The gold standard for BSIs etiologic diagnosis is represented by the blood cultures followed by conventional pathogen identification and antimicrobial susceptibility testing. Unfortunately, even accelerating and tightly monitoring the pre-analytic and analytic phases [68], blood cultures turnaround-time is often long. In the last decades, the average reporting time of blood cultures results has been significantly shortened by the introduction of blood cultures automated monitoring systems and MALDI-TOF-based microbial identification [69,70].…”
Section: Bloodstream Infections At the Emergency Departmentmentioning
confidence: 99%